1972
DOI: 10.1021/ic50114a050
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of the complex di-.mu.-hydroxo-bis[2-(2-ethylaminoethyl)pyridine]dicopper(II) perchlorate

Abstract: NotesScheme I category IV reactions should have similar values for the rate constants, as is observed.The rate constant calculated for reaction 1 in Table III lies well in the diffusion-controlled region and seems prohibitively high. It should be noted, however, that the value given in Table III is only about two or three times greater than the values for Cu(II)-en reactions given in Table II or reported by Kirschenbaum and Kustin13for25°.The high rate constants are the direct result of attributing "normal" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…It has been shown that exchange interaction is affected by several structural parameters such as the identity of the bridging atoms (X), the Cu-Cu' distances, the bridging angles Cu-X-Cu' (α), the dihedral angles containing Cu ions and the coordination geometries around copper ions. 5,9,[45][46][47][48][49] For planar dihydroxo-bridged copper complexes, a simple, linear, correlation between the singlet-triplet separation 2J and the angle α was reported. [45][46][47] However, in the case of dihalo-bridged copper complexes, the wider variety of geometries available to such systems and the possibility for relatively low-lying halogens' d-orbitals to interact with copper orbitals make the overall picture more complicated.…”
Section: Magneto-structural Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that exchange interaction is affected by several structural parameters such as the identity of the bridging atoms (X), the Cu-Cu' distances, the bridging angles Cu-X-Cu' (α), the dihedral angles containing Cu ions and the coordination geometries around copper ions. 5,9,[45][46][47][48][49] For planar dihydroxo-bridged copper complexes, a simple, linear, correlation between the singlet-triplet separation 2J and the angle α was reported. [45][46][47] However, in the case of dihalo-bridged copper complexes, the wider variety of geometries available to such systems and the possibility for relatively low-lying halogens' d-orbitals to interact with copper orbitals make the overall picture more complicated.…”
Section: Magneto-structural Correlationmentioning
confidence: 99%
“…5,9,[46][47][48][49][50] For planar dihydroxo-bridged copper complexes, a simple, linear, correlation between the singlet-triplet separation 2J and the angle α was reported. [46][47][48] However, in the case of dihalo-bridged copper complexes, the wider variety of geometries available to such systems and the possibility for relatively low-lying halogens' d-orbitals to interact with copper orbitals make the overall picture more complicated. 51 Generally, a strong correlation ( parabolic curve with a maximum of ca.…”
Section: Magneto-structural Correlationmentioning
confidence: 99%
“…-205 (12) 1323 ( 23) 414 ( 7) Br( 2) 3705 (4) 394( 4) 2803 (27) -447 (11) 1403 (3) 13( 8) 0(1) 209 (15) 21 (2) 81( 7) 6 (5) 58( 9) 12 (3) C(l) 176 ( 26) 44 ( 4) 125 ( 14)…”
Section: Dicussionunclassified
“…Hatfield Jeter, Lewis, Hempel, Hodgson & Hatfield, 1972) and similar studies on the analogous systems [Cu(bipy)OH] 2+, where bipy is 2,2'-bipyridine (Casey, Hoskins & Whillans, 1970;Majeste & Meyers, 1970;Barnes, Hodgson & Hatfield, 1972) and [Cu(tmen)OH] 2+, where tmen = tetramethylethylenediamine (Mitchell, Bernard & Wasson, 1970;Cole & Brumage, 1970) we were able to deduce that the value of 2J, the singlet-triplet energy separation, decreases as the Cu-O-Cu bridging angle ~0 increases, and that 2J changes from positive to negative in the region 97 to 99 ° .…”
Section: Introductionmentioning
confidence: 99%